Educational constraints on marital sorting and income mobility - Nan Gao (PLoS ONE, 2025)
This paper examines the effect of educational assortative mating on overall income mobility in terms of both inter- and intragenerational mobility. In recent years, educational assortative mating has become a trend in China, and this marital sorting pattern not only contributes to marriage stability but is also related to increased income mobility. Educational assortative mating affects the distribution of educational resources among families with diffferent educational qualifications. Families with higher educational qualifications have more educational resources, thus obtaining a more solid income status. Educational assortative mating has the most significant influence on the income mobility of the low-income group, as high-quality educational resources are the key to enabling this group to raise its income status. This paper argues that, in the future, income mobility should be promoted by evenly distributing social education resources and reducing the resource constraints on the upward mobility of the low-income group.